Problems in Teaching Programming to Pupils at General Secondary Education Institutions and the Ways to Solve Them Using an Open Educational Resource - Rudyk, Оleksandr (Educological discourse, 2024)
Globalisation of the world economy, in the context of the increasing significance of computer technology, presents novel challenges for the domain of education, one of which is teaching programming to students of general secondary education institutions. The article deals with the problems of such teaching. The primary focus of the study of the basis of designing as well as using software is justified. The problem of the absence of preconditions for the successful study of natural sciences and mathematics in general and teaching of programming in particular in most schools is analysed within the framework of the competence approach. This study examines the factors that contribute to the low motivation for learning programming which results in isolation of the learning process from the requirements of the software market, including the choice of software and the possibility of switching between different types of software. The study reveals the factors that contribute to the negative attitude of the majority of teachers towards quality programming education. The results of the study of teachers’ attitudes to the analysed problems are presented. The data provide an opportunity to draw a conclusion regarding the teachers’ ideas about the sequence of mastering procedural and object-oriented programming skills, as well as their ability to teach algorithms formulation. Dissatisfaction with the available teaching and methodological support of the vast majority of teachers is revealed. Teachers’ attitudes towards mastering programming languages, relevant for the modern software industry, is studied. A comprehensive solution to those problems that can be overcome within the framework of computer science education is proposed, which consists in the use of open educational resources with high content quality requirements. The study provides a link to the example of the completed project of educational and methodological support for the study of information technologies only on the basis of freely distributed software, as well as the current project for studying the basics of programming using various programming environments. It is important to note that the proposed approaches are not rigidly implemented in education system in Ukraine, and, therefore, this experience can be easily broadened to other countries and (if necessary) to other disciplines.